An insight into the extragalactic transient and variable microJy radio sky across multiple decades. Issue 3 (18th October 2019) - Radcliffe, Jack F; Beswick, Robert J; Thomson, A P; Garrett, Michael A; Barthel, Peter D; Muxlow, Thomas W B
ABSTRACT: The mJy variable extragalactic radio sky is known to be broadly non-changing with approximately $3{{\ \rm per\ cent}}$ of persistent radio sources exhibiting variability that is largely active galactic nucleus-related (AGN). In the faint (<mJy) flux density regime, it is widely accepted that the radio source population begins to change from AGN dominated to star formation dominated, together with an emergent radio-quiet AGN component. Very little is known about the variable source component in this sub-mJy regime. In this paper, we provide the first insight into the μ Jy variable sky by performing a careful analysis using the deep VLA data in the well-studied GOODS-N field. Using five epochs spread across 22 yr, we investigate approximately 480 radio sources finding 10 that show signs of variability. We attribute this variability to the presence of an AGN in these systems. We confirm and extend the results of previous surveys, finding that variability in the faint radio sky is rather modest with only ≤2 per cent of sources exhibiting significant variability between any two epochs. We find that 70 per cent of variable sources show variability on time-scales of a few days while on longer decadal time-scales, the fraction of variable sources decreases to $\lt 1{{\ \rm per\ cent}}$ . This suggests that the radio variability peaks on shorter time-scales as suggested by other studies. We find that 80 per cent of variable sources have VLBI counterparts, and we use multiwavelength data to infer that these may well be core-dominated FR-I sources as postulated by the wide-field VLBI surveys and semi-empirical simulations.